The Use of Intellectual Property Rights as Collateral for Debt: Legal Regulations and Valuation Analysis - Annisa Fitria; Rita Alfiana; Mira Kartika Dewi Djunaedi; Zummiyanuran Habibi; Alyana Marsyanda (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to examine the legal regulations governing IPR as collateral for debt, and how to determine the valuation of IPR used as collateral. The study method used is normative law with a legislative and conceptual approach. Data was obtained through a literature study of primary and secondary legal materials. The novelty of this study lies in its focus on the legal vacuum and implementation constraints in the field in making IPR, particularly copyright, an object of fiduciary collateral, especially in terms of economic valuation and ownership validity. The results of the study show that although Indonesian fiduciary law has normatively recognized the possibility of using IPR as collateral, in practice financial institutions still face various obstacles. This is partly due to the absence of standard assessment criteria, issues of proof of ownership, and a declarative IPR registration system. The conclusion of this study is that IPR has economic potential and a legal basis as collateral for debt, but it still requires specific derivative regulations and a clear economic value assessment mechanism in order to be widely accepted by financial institutions. The development of this policy is important to support the sustainable financing of the creative economy sector.